2010
DOI: 10.1111/j.1399-3054.2010.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and phylogenetic analysis of two new lycopene β‐cyclases from Citrus paradisi

Abstract: Two new lycopene β-cyclases (LCYBs) were cloned and characterized from grapefruit (Citrus paradisi Macf.). During fruit ripening, CpLCYB1 expression did not show significant differences between 'Flame' (red flesh) and 'Marsh' (white flesh), and was much lower than CpLCYB2 and nearly constant; however, CpLCYB2 expression dramatically changed in a similar tendency in the pulp of both grapefruit cultivars, but the relative abundance of mRNA in 'Flame' was significantly lower than in 'Marsh'. Phylogenetically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The peel of red grapefruits also contains lycopene and, as in the pulp, it has been hypothesized that its accumulation could be related to specific sequestration structures (Xu et al, 2006) and/or to a pathway blockage at the ␤-carotene synthesis (Fanciullino et al, 2006). More recently, molecular data indicated that in red and pink grapefruits accumulation of lycopene and ␤-carotene during maturation is associated with a reduced expression of the chromoplast-specifič -LCY2 gene and also ˇ-CHX in comparison with sweet orange (Alquezar et al, 2009) or white grapefruit (Mendes et al, 2011;Alquezar et al, 2013). Two alleles of ˇ-LCY2 gene have been identified, with high (ˇ-LCY2a) and low (ˇ-LCY2b) lycopene cyclase activity (Alquezar et al, 2009).…”
Section: Lemon (Citrus Lemon) and Lime (Citrus Aurantifolia Citrus Lmentioning
confidence: 99%
“…The peel of red grapefruits also contains lycopene and, as in the pulp, it has been hypothesized that its accumulation could be related to specific sequestration structures (Xu et al, 2006) and/or to a pathway blockage at the ␤-carotene synthesis (Fanciullino et al, 2006). More recently, molecular data indicated that in red and pink grapefruits accumulation of lycopene and ␤-carotene during maturation is associated with a reduced expression of the chromoplast-specifič -LCY2 gene and also ˇ-CHX in comparison with sweet orange (Alquezar et al, 2009) or white grapefruit (Mendes et al, 2011;Alquezar et al, 2013). Two alleles of ˇ-LCY2 gene have been identified, with high (ˇ-LCY2a) and low (ˇ-LCY2b) lycopene cyclase activity (Alquezar et al, 2009).…”
Section: Lemon (Citrus Lemon) and Lime (Citrus Aurantifolia Citrus Lmentioning
confidence: 99%
“…Highlevel expression of LCYb genes shifts the flux of the pathway to the b-branch during the orange stage (Kato et al, 2004;Zhang et al, 2012;Rodrigo et al, 2013). Additionally, reductions in the transcript levels of a chromoplast-specific LCYb gene are responsible for the substantial accumulation of lycopene in the pulp of sweet orange (Citrus sinensis; Lu et al, 2016b) and grapefruit (Citrus paradisi;Alquézar et al, 2009;Mendes et al, 2011). However, whether and how the expression of the citrus LCYb genes is regulated by the ripeningassociated regulators that are mentioned above are not clear.…”
mentioning
confidence: 99%
“…It was different from CsLCYB1 that was expressed at low levels and remained relatively constant during fruit ripening [67]. One allele of CsLCYB2, expressed only in normally pigmented fruits, has normal LCYB activity, while the other, preferentially expressed in red-fleshed grapefruit, loses that activity and likely leads to the lycopene accumulation [63,67]. "Hong Anliu" has a 1000-fold higher lycopene accumulation in the albedo, segment membranes, and juice sacs than its wild type, but no change of carotenoid composition in leaves.…”
Section: Comparative Genomics In Lycopene-enriched (Red-fleshed) Fruitsmentioning
confidence: 96%
“…Some of these cultivars have unusually high lycopene accumulation that results in deep red flesh, and these have been top choices to study the molecular mechanisms of the flux of the relevant pigments, including "Cara Cara" navel orange [30,31,[55][56][57], "Hong Anliu" sweet orange [58][59][60][61][62], and "Flame" and other red grapefruits [19,63,64]. They are also widely cultivated in certain regions primarily for fresh consumption because of visual appeal and the presumed health benefits of lycopene and sweeter taste in red grapefruits [65,66].…”
Section: Comparative Genomics In Lycopene-enriched (Red-fleshed) Fruitsmentioning
confidence: 99%